2019
DOI: 10.1007/s40199-019-00265-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Echinacea purpurea (Immulant) against cisplatin-induced immunotoxicity in rats

Abstract: Purpose Cisplatin, one of the most effective anticancer drugs, is known to cause undesirable adverse effects, including immunotoxicity. Echinacea purpurea is an important medicinal plant with immunostimulatory and anti-inflammatory activities. We have investigated the protective effect of an herbal formulation (Immulant) containing E. purpurea extract against cisplatininduced immunotoxicity in rats. Methods Forty mature albino rats were randomized into four groups (10 rats/group). Control (group 1) animals wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
(39 reference statements)
2
16
0
1
Order By: Relevance
“…Table 7. Mean background contents of trace elements in surface soils (Khalaf et al 12 ). www.nature.com/scientificreports/ Increasing the NO 3 − concentration leads to increase of release rate over time.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table 7. Mean background contents of trace elements in surface soils (Khalaf et al 12 ). www.nature.com/scientificreports/ Increasing the NO 3 − concentration leads to increase of release rate over time.…”
Section: Resultsmentioning
confidence: 99%
“…According to Saeed et al (2018), accumulation of phenolic compounds in the plant rhizomata cum radicibus prevents NO 3 − toxicity in plants. There are some reports showing that stress conditions increase either phenylalanine ammonia lyase (PAL) synthesis or activity in plants 6,11,12,14,32 ; other authors 24 have found that some stress treatments delay the increase in wound-induced PAL activity. Phenylalanine Ammonia-Lyase activity was found to vary greatly with the stage of plant development 18 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations